Energy and material recovery of kraft paste bleaching effluents - Silva, Nuno André Araújo (2022)
Anaerobic digestion is a treatment process applied to organic solid waste and wastewater carried out by microorganisms under anaerobic conditions (without oxygen). In addition to treating wastewater, this process’s main product is biogas, a mixture of methane and carbon dioxide. On this assumption, it is easy to understand how this biological process can be an asset in the fight against climate change, as it not only produces renewable energy, but also contributes to reducing the negative impacts resulting from the discharge of organic waste into the environment. The main objective of this work was to study the acidogenic and methanogenic anaerobic processes applied to an industrial effluent with low biodegradability and with potentially inhibitory compounds for the production of materials, such as VFAs, and energy (methane), respectively. The effluent under study was the bleaching effluent from the Kraft pulp production process, denominated D0, which contains, among other recalcitrant materials, AOX compounds. The influence of operational parameters in maximization of these products and increasing the aerobic biodegradability of the treated effluent were also analyzed. To study the process of anaerobic digestion of the D0 effluent, two reactors with magnetic and mechanical agitation, and volumes of 1.75 l and 7 l, respectively, operating in the mesophilic temperature range were set up. Four runs were carried out, with different feed pH values: pH 3, 4, 6 and 7. The best results in sCOD and AOX removal efficiencies were obtained at influent pH 4, which removed 58% of the first and 63% of the second, using an HRT of 1.461 days (the lowest used in all operations) and 6 different loads (between 0.419 gCOD l−1 day−1 and 1.282 gCOD l−1 day−1). The production of methane was also better at this feed pH. The aerobic biodegradability of the effluent was improved in all four operations carried out, with the greatest increase also being achieved in the test with pH 4 in the feed (4.5 times increase). Therefore, this pH range in the feed is the most suitable for the treatment of this type of effluent.